Invaders of pollination networks in the Galapagos Islands: emergence of novel communities - Traveset, A. (2013)
The unique biodiversity of most oceanic archipelagos is currently threatened by the introduction of alien species that can displace native biota, disrupt native ecological interactions, and profoundly affect community structure and stability. We investigated the threat of aliens on pollination networks in the species-rich lowlands of five Galápagos Islands. Twenty per cent of all species (60 plants and 220 pollinators) in the pooled network were aliens, being involved in 38 per cent of the interactions. Most aliens were insects, especially dipterans (36%), hymenopterans (30%) and lepidopterans (14%). These alien insects had more links than either endemic pollinators or non-endemic natives, some even acting as island hubs. Aliens linked mostly to generalized species, increasing nestedness and thus network stability. Moreover, they infiltrated all seven connected modules (determined by geographical and phylogenetic constraints) of the overall network, representing around 30 per cent of species in two of them. An astonishingly high proportion (38%) of connectors, which enhance network cohesiveness, was also alien. Results indicate that the structure of these emergent novel communities might become more resistant to certain type of disturbances (e.g. species loss), while being more vulnerable to others (e.g. spread of a disease). Such notable changes in network structure as invasions progress are expected to have important consequences for native biodiversity maintenance.